Identification of Capsicum accessions tolerant to Tomato severe rugose virus and resistant to Bemisia tabaci Middle East-Asia Minor 1 (MEAM1) - Pantoja, Kessia F. C. [UNESP]; Rocha, Kelly C. G. [UNESP]; Melo, Arlete M. T.; Marubayashi, Julio M. [UNESP]; Baldin, Edson L. L. [UNESP]; Bentivenha, Joao P. F. [UNESP]; Gioria, Ricardo; Kobori, Romulo F.; Pavan, Marcelo A. [UNESP]; Krause-Sakate, Renate [UNESP] (Springer, 2018)
The whitefly Bemisia tabaci is one of the most important pests of solanaceous crops worldwide, mainly due to its ability to transmit different viruses, including begomoviruses. Tomato severe rugose virus (ToSRV) is the prevalent begomovirus in southeastern and central Brazil, and affects economically important vegetable crops such as tomato and pepper. Here we evaluated 36 pepper accessions comprising four species (Capsicum annuum, C. frutescens, C. chinense and C. baccatum) for ToSRV and B. tabaci resistance, through free-choice and non-choice tests. The accessions IAC-1544 (C. frutescens), IAC-1545 and 1549 (C. chinense), IAC-1551, 1566 and 1579 (C. annuum) were infected by ToSRV but did not show any symptoms. Among them, IAC-1544, IAC-1545, IAC-1551 and IAC-1579 displayed significant differences in whitefly egg-laying preference in the free-choice test. In the non-choice test, IAC-1544, IAC-1545 and IAC-1579 displayed similar reaction, being unattractive to the insects and exhibiting reduced oviposition rates. Low survival of nymphs and high mortality were observed in accessions IAC-1544, IAC-1545, IAC-1549, IAC-1551, IAC-1566 and IAC-1579, suggesting the involvement of antibiosis mechanisms. The accessions IAC-1544, IAC-1545 and IAC-1579 could be classified as good sources of resistance to both ToSRV and B. tabaci.
Keywords: Sweet pepper; Whitefly; Bemisia tabaci biotype B